Scientific Knowledge about Poultry Broiler Farming in Barabanki District of Uttar Pradesh (Indian Journal of Extension Education, 2017)
The present investigation was carried out to study the scientific knowledge about broiler farming among poultry farmers in Barabanki district of Uttar Pradesh. Fifteen poultry farmers were selected randomly from each block, making a total sample size of 75. To measure the knowledge level of respondents with regard to scientific broiler farming practices, a structured pretested interview schedule was developed consisting of 72 objective type questions related to seven major areas like housing, brooding, feeding, bio-security and disease control, finance, marketing and poultry insurance. Every correct answer was given score one and incorrect score zero. The total knowledge score of the respondent was obtained by adding scores of all the correct answers out of 72 questions. The lowest score that a respondent could obtain was zero and the highest was 72. On the basis of overall knowledge score, the respondents were classified into three categories as low, medium and high on the basis of equal interval between maximum and minimum knowledge score. The study revealed that all the small poultry farmers had medium level of scientific knowledge about feed and feeding management practices, housing management practices and brooding management practices (in overwhelming majority), while all the large poultry farmers had high level of scientific knowledge about housing management practices, breed selection and identification of quality chicks, feed and feeding management practices and poultry insurance. All the medium poultry farmers were found to have medium level of scientific knowledge about bio-security and disease control practices, finance, marketing and poultry insurance, while overwhelming majority of them (93.75%) were having high level of knowledge about feed and feeding management practices. Majority of medium poultry farmers were found to possess medium level of knowledge about brooding management, breed selection and identification of quality chicks while, high level of knowledge about housing management practices. Majority of them had high level of knowledge about feed and feeding management practices. Further, comparison of knowledge level about scientific broiler farming among the different categories of poultry farmers using one way ANOVAwas also done and the results show that small, medium and large poultry farmers were found to differ significantly at 1per cent level of significance (p<0.01) with respect to knowledge about scientific broiler farming practices.